1997
DOI: 10.1074/jbc.272.50.31515
|View full text |Cite
|
Sign up to set email alerts
|

Role of Translocation in the Activation and Function of Protein Kinase B

Abstract: We have investigated the role of subcellular localization in the regulation of protein kinase B (PKB) activation. The myristoylation/palmitylation motif from the Lck tyrosine kinase was attached to the N terminus of protein kinase B to alter its subcellular location. Myristoylated/palmitylated (m/p)-PKB␣ was associated with the plasma membrane of transfected cells, whereas the wild-type kinase was mostly cytosolic. The activity of m/p-PKB␣ was 60-fold higher compared with the unstimulated wild-type enzyme, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

46
794
5
13

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 953 publications
(865 citation statements)
references
References 50 publications
46
794
5
13
Order By: Relevance
“…This view is partially supported by the fact that we observe no redistribution of SRK following EGF stimulation of quiescent cells. Also, recent reports revealed that Akt, a possible upstream regulator for both SRK (Figure 4) and p70S6K (Burgering and Co er, 1995;Kohn et al, 1996), translocates from the plasma membrane to the nucleus after stimulation with mitogens, and phosphorylates nuclear as well as cytoplasmic targets (Andjelkovic et al, 1997). However, we cannot exclude the possibility that there exist separate signaling pathways which regulate SRK and p70S6K.…”
mentioning
confidence: 69%
“…This view is partially supported by the fact that we observe no redistribution of SRK following EGF stimulation of quiescent cells. Also, recent reports revealed that Akt, a possible upstream regulator for both SRK (Figure 4) and p70S6K (Burgering and Co er, 1995;Kohn et al, 1996), translocates from the plasma membrane to the nucleus after stimulation with mitogens, and phosphorylates nuclear as well as cytoplasmic targets (Andjelkovic et al, 1997). However, we cannot exclude the possibility that there exist separate signaling pathways which regulate SRK and p70S6K.…”
mentioning
confidence: 69%
“…Although Akt is mainly cytosolic, a relevant fraction is also found in the nucleus, particularly of the activated form (Ahmed et al, 1993;Andjelkovic´et al, 1997). Both cytosolic and nuclear Akt activities were upregulated in Snail1-transfected cell lines (Figure 1b), an effect that, again, was more remarkable in serum-depleted cells.…”
Section: Snail1 Induces Akt Activation In Tumor Cell Linesmentioning
confidence: 83%
“…Although Akt proteins localize predominantly in the cytoplasm, they also reside in the nucleus or translocate to this compartment upon stimulation (Ahmed et al, 1993;Andjelkovic´et al, 1997). In the nucleus Akt phosphorylates or interacts with proteins implicated in apoptosis resistance, a pathway where Akt has a key role (Andjelkovic´et al, 1997;Masuyama et al, 2001;Ahn et al, 2006;Lee et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akt is initially activated at the cell membrane in response to stimulation by growth factors, such as insulin‐like growth factor 1 (IGF1) (Alessi et al ., 1996). After activation, Akt phosphorylates multiple cytosolic substrates and translocates to nucleus, where it is thought to regulate gene transcription (Andjelkovic et al ., 1997; Brazil et al ., 2002). Mammals express three isoforms of Akt; Akt1 and Akt2 are expressed ubiquitously, whereas Akt3 is found predominantly in the brain, kidney, and heart (Datta et al ., 1999; Masure et al ., 1999).…”
Section: Introductionmentioning
confidence: 99%